Has china won? The chinese challenge to american primacy - Aslan, Halil Kürşad (Taylor and Francis Ltd., 2022)
There are several interpretations of the Sino-American rivalry and predictions about the emerging new world order, including from Graham Allison, John Mearsheimer, and Steven Walt amongst others. Kishore Mahbubani adds to the discussion by setting out a general outline of the rivalry and relative strengths and weaknesses of the two countries. According to him, the United States has five strategic advantages: individual empowerment as a land of opportunity, access to humanity’s ‘best and brightest’, the best universities – intellectual ecosystems – strong political institutions, and membership of Western civilisation.
Keywords: American Primacy; Chinese Challenge; China